Application of microfluidics in biosensors - Wang, Jing; Ren, Yong; Zhang, Bei (IntechOpen, 2020)
This chapter reviews the up-to-date researches in the field of biosensors integrated with microfluidic techniques, most of which are research works published within the last five years. The trend of integrating microfluidics into biosensing technologies is analyzed, as the features of microfluidics fulfills the technical requirements recently raised in the field of healthcare. The current research works are discussed in details based on the biological recognition events and the transduction mechanism. Their pros and cons are discussed. The potential of microfluidics-integrated biosensors are prospective and their future applications in the field of healthcare is revolutionary, for example in the field of portable and wearable biosensor, which can be fabricated at extremely low cost ad require no professional operation, and this can widen the application of biosensor especially for remote districts and extreme poverty populations. The possible future research interests in this field are proposed in this chapter.